Defective 30S Ribosomal Subunits After Infection of Escherichia coli by T2 Ghosts - Simon, Michel (1974)
Ribosomes from ghost-treated Escherichia coli can form in vitro initiation complexes but cannot translate added template RNA because of a defect in the 30S subunit; 16S rRNA is degraded.